Investigating mechanisms for recruiting and retaining volunteers: The role of habit strength and planning in volunteering engagement. Issue 3 (4th May 2021) - Mullan, Barbara; Liddelow, Caitlin; Charlesworth, Jessica; Slabbert, Ashley; Allom, Vanessa; Harris, Courtenay; Same, Anne; Kothe, Emily
ABSTRACT: Volunteering rates in high-income countries are declining. Most research into understanding volunteering engagement has focused on conscious processes (e.g., motives), with little exploration of non-conscious antecedents of volunteering engagement. Adopting a new line of investigation, this research used temporal self-regulation theory to investigate the influence of both rational and automatic processes on volunteering engagement. Two related studies using different methodologies were conducted to investigate the influence of intention, planning, and habit strength on volunteering engagement. In both studies, intention and habit strength were significant predictors of volunteering engagement, with planning only significantly predicting volunteering engagement in Study 1. It was also found, in Study 2, that habit strength moderated the intention–behavior relationship. These findings highlight that both rational and automatic processes play a part in volunteering engagement and have implications for recruiting and retaining volunteers.